2021
DOI: 10.3390/cancers13071598
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Local Liver Irradiation Concurrent Versus Sequential with Lenvatinib on Pharmacokinetics and Biodistribution

Abstract: Concurrent and sequential regimens involving radiotherapy (RT) and lenvatinib were designed with off-target or stereotactic body radiation therapy (SBRT) doses in a freely moving rat model to evaluate the effect of RT on the pharmacokinetics (PK) of lenvatinib. Liver RT concurrent with lenvatinib decreased the area under the concentration–time curve of lenvatinib concentration (AUClenvatinib) by 51.1% with three fractions of 2 Gy (RT2Gy×3f’x, p = 0.03), and 48.9% with RT9Gy×3f’x (p = 0.03). The AUClenvatinib i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Moreover, the primary sources of ROS in the liver are the mitochondria and cytochrome P450 enzyme systems and derive from Kupffer and inflammatory cells ( 15 ). Additionally, drug pharmacokinetics influenced by RT has previously been revealed ( 16 , 17 ). Breast cancer patients treated by advanced RT could experience off-target exposure to surrounding organs such as the lung and heart, which might cause unpredictable effects ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the primary sources of ROS in the liver are the mitochondria and cytochrome P450 enzyme systems and derive from Kupffer and inflammatory cells ( 15 ). Additionally, drug pharmacokinetics influenced by RT has previously been revealed ( 16 , 17 ). Breast cancer patients treated by advanced RT could experience off-target exposure to surrounding organs such as the lung and heart, which might cause unpredictable effects ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer patients treated by advanced RT could experience off-target exposure to surrounding organs such as the lung and heart, which might cause unpredictable effects ( 18 , 19 ). Recently, RT significantly impacted the hepatic microsomal cytochrome P450 3A4 (CYP3A4) activity and P-glycoprotein (P-gp) activity ( 16 , 17 ). This was likely caused by an unintended interaction between RT and tamoxifen.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Dawson et al [ 20 ] reported that SBRT followed by sorafenib improved the overall survival, progression-free survival and time to disease progression compared with sorafenib alone for HCC patient. Moreover, our previous data showed that RT modulated PK of TKIs [ 19 , 21 , 22 ] and supported the interaction between RT and TKIs.…”
Section: Introductionmentioning
confidence: 55%
“…Similarly, the AUC of regorafenib was increased 1.3-fold in the sequential RT 9Gyx3f’x group [ 21 ]. The AUC of lenvatinib was increased 2-fold in the sequential RT 9Gyx3f’x group [ 22 ]. The lines of evidence support the interaction between RT and TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Wild et al [ 36 ] demonstrated that sequential sorafenib treatment after radiotherapy appears to be more effective for HCC. For lenvatinib combined with radiotherapy, a study of the pharmacokinetic and biodistribution effects of simultaneous or sequential lenvatinib with local liver irradiation in a freely moving rat model [ 37 ] demonstrated that a sequential regimen has a greater ability to maintain lenvatinib uptake compared to a simultaneous regimen, and that sequential regimens may be more impactful than concurrent regimens. However, there are fewer studies on the sequence of radiotherapy combined with TKIs, and further evidence is needed to elucidate the impact of the sequence between the two on treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%